A COMPARATIVE STUDY OF VARIOUS DISTANCE MEASURES IN INTUITIONISTIC FUZZY SETS AND THEIR EXTENSIONS - BEGUM*, SYED SIDDIQUA; SRINIVASAN, R. (International Journal of Mathematical Archive, 2018)
In this paper, we define the Hamming distance measure and normalized Hamming distance measure of Intuitionistic Fuzzy Sets of Second Type and Intuitionistic Fuzzy Sets of Third Type. Also the comparison is made between the measures.